Bacillus Spp. Amylase: Production, Isolation, Characterisation and Its Application - Sachdev, Shivani; Ojha, Sanjay Kumar; Mishra, Snehasish (International Journal of Applied Sciences and Biotechnology, 2016)
Amylase is one of the leading enzymes used in industry from decades. The preliminary function of this enzyme is the hydrolysis of the starch molecule into glucose units and oligosaccharides. Amylases have spectacular application in broad spectrum of industries such as food, detergent, pharmaceutical and fermentation industries. Among different type of amylases α- amylase is in utmost demand because of its striking features. This particular enzyme is a good substitute over the chemicals catalyst used in industries. α- amylases can be acquired from different sources such as microorganism, animals and plants. Microorganisms are the major source of production of amylase because of the ease of availability, manipulation and operation. The starch converting enzymes is basically generated using submerged fermentation. Some of the prominent characteristics of amylase are its mode of action, substrate specificity and operating condition (temperature and pH). Amylases from different bacterial sources contribute differently to the particular trait of the enzyme. Bacillus amylases have been studied and applied so far because of their robustness in nature and easy accessible pure form of it. Thus this makes it more specific and fit for distinct application in the industry. The purpose of this manuscript was the comparative analysis of the physical and chemical features of α amylases from Bacillus species. It also focuses on the unique characteristics of this enzyme and their industrial applications. Int J Appl Sci Biotechnol, Vol 4(1): 3-14